Ammonia decomposition catalysis using non-stoichiometric lithium imide1. Issue 7 (15th July 2015) - Makepeace, Joshua W.; Wood, Thomas J.; Hunter, Hazel M. A.; Jones, Martin O.; David, William I. F.
<x xml:space="preserve">Abstract</x> The non-stoichiometric lithium imide–amide system effectively decomposes ammonia to its constituents, hydrogen and nitrogen. Isotopic studies show that this bulk catalytic reaction has the potential to generate high-purity hydrogen for future energy and transport applications.